Transformacja potencjału akademickiego w ujęciu regionalnym - Nowakowska, Aleksandra (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
In the contemporary - knowledge-based economy, human capital became the key factor of dynamic and sustainable economic development. The higher education system and academic potential are the important elements of building the capital of this kind. The changes, which were undertaken during the transformation of the economical system of the country, transfigured radically their academic potential. Development of private academic institutions, new majors and new types of schools, introduction of direct payments for selected educational services and the fact, that tertiary education became widespread in our society, seem to be the most important reasons of success of transformation of the country' s academic potential. Dynamic development of higher education implicates both positive and negative effects. At regional level of the country, visible disparities in development of academic potential can be observed. This process strengthens already existing regional inequality. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 210-220